SYNTHESIS OF POLYEUGENYL OXYACETIC ACID AS A CARRIER TO SEPARATE HEAVY METAL ION Fe (III), Cr(III), Cu(II), Ni(II), Co(II), AND Pb(II) THAT USING SOLVENT EXTRACTION METHOD - La Harimu; Sabirin Matsjeh; Dwi Siswanta; Sri Juari Santosa (Universitas Gadjah Mada, 2009)
Polyeugenyl oxyacetic acid has been synthesized from polyeugenol and chloroacetic acid and applied to separate metal Fe(III), Cr(III), Cu(II), Ni(II), Co(II), and Pb(II) using solvent extraction method. pH effect, polyeugenyl oxyacetic acid ion carrier concentration, extraction time, and metal concentration optimized to gain optimum condition. The result of experiment indicated that polyeugenyl oxyacetic acid resulted the yellowed brown synthesis with melting point 125 °C and yield 68.9%. The Characterization of spectroscopy IR attributed by absorption to the area 1735,8 cm -1 as carbonyl extend vibration (C=O) acid and 1H-NMR that was attributed by chemical shift at 4.6 ppm as carboxy proton (CH2-C=0). The metal separation optimum condition gained pH 3-6 for ion Fe(III), pH 5 for ion Cr(III), Ni(II), and Co(II) and pH 6 for ion Cu(II), and Pb(II). Optimum carrier concentraction 5 mL, 10 mL, and 15 mL for ion Fe(III), and ion Cr(III), Ni(II), Co(II), and ion Cu(II), Pb(II) respectively. Extraction time 2.5 h for ion Fe(III), 20 h for ion Cr(III), and 36 h for ion Cu(II), Pb(II), Ni(II), and Co(II). Metal concentration that would extracted correctly (0.75-5 x 10-4 M) for ion Fe(III), (0.75-2.5 x 10-4 M) for ion Cr(III), Ni(II), and Co(II) and (0.75-1 x 10-4 M) for ion Cu(II) and Pb(II). The best polyeugenil oxyacetic acid response to separate ion Fe(III) than other ions with selectivity order Fe(III)> Cr(III)> Cu(II)> Pb(II)> Ni(II)> Co(II).